Elsevier's encyclopedia of neuroscience - Adelman, George; Smith, Barry H. (Amsterdam : Elsevier Science, 1999)
Includes more than 800 contributions, over 14,000 EMBASE abstracts, direct access to relevant WWW sites, animations videos, and other illustrations
CD is available at Koleksi Media, Perpustakaan HUKM
System requirements for Macintosh: 68030 or better processor; System 7 or better
Keywords: Neurosciences -- Encyclopedias -- English